Immunological phenomena in the jejunum and serum after reintroduction of dietary gluten in children with treated coeliac disease. Issue 7 (July 1976) - Lancaster-Smith, M; Packer, S; Kumar, P J; Harries, J T
Abstract : Jejunal mucosal immunoglobulin-containing cells of all three major classes (IgA, IgM, IgG) were increased in coeliac children on gluten-containing diets but only IgM cell numbers were raised in those on gluten-free diets. Patients with subtotal villous atrophy had greater numbers of immunoglobulin-containing cells than patients with normal mucosa. In previously treated patients studied before and after three months on a gluten-containing diet ther was an increase in all three classes of cell, IgM containing cells showing the greatest proportional rise. Basement membrane staining with anti-IgA serum occurred in coeliacs and was most intense in untreated patients. Apart from one patient with very low levels of serum IgA, serum immunoglobulins did not differ from normal. However, after reintroduction of gluten to the diet a significant fall in serum IgM concentrations occurred compared with levels in the same patients while on gluten-free diets. It seems probable that both IgA and IgM systems are important in the immunopathogenesis of the small intestinal lesion of childhood coeliac disease.